Peran Emosi Terhadap Rasionalitas dan Pembelian Impulsif Studi Kasus pada Mahasiswa Universitas Silampari - Tamri Tamri; Erwandi R; Iskandar D; Slamat J (Journal of Management and Bussines (JOMB), 2023)
The aim of this research is to determine the influence of emotions on rationality and impulsive buying. This study uses a quantitative approach. The target population in this research was students at Silampari University, Lubuklinggau, totaling 115 respondents. After processing it was found that 111 respondents were acceptable. Processed using smartpls-4. Research results Respondents were more likely to use instant messaging applications to connect with family members, followed by friends from far away or from college (mean = 3.84), and buyers or sellers (mean = 3.18). Furthermore, respondents indicated that they use instant messaging apps more often to send messages (mean = 3.89), followed by updating others on where they are now doing (mean = 3.16), posting social post quotes ( mean = 2.66), and convey their feelings in words (mean = 2.66). In conclusion, the majority of respondents have used instant messaging for more than two years, with an average of three years using instant messaging to make purchasing interactions with sellers. This increases the likelihood of the urge to buy impulsively. Keywords: Positive Emotions, Positive Normative Evaluation, Impulsive Buying